PEMURNIAN GALUR KACANG HIJAU (Vigna radiata L.) LOKAL KAMPAR GENERASI KEEMPAT - Herman Herman; Misriyani Misriyani; Dewi Indriyani Roslim (UIR Press, 2016)
Kampar Regency is one of the areas of mungbean production in Riau Province. As a germ-plasmin genetic diversity, Kampar mungbean is a local variety that can produce high yield mungbean cultivar. The color of pods and seeds of mungbean may affect the consumer taste. The research was aimed to give information about genetic diversity of Kampar local mungbean and its use as a germ-plasm resource to produce a new cultivar with high yield trait. The research was conducted from August to November 2015 at the Biology garden, Faculty of Mathematics and Science, University of Riau. The randomized complete design with 9 lines and 5 replications was used. The result showed the G0, G1, G2, G5, G6, G7, and G8 lines produced black color pods, while G3 line produced blackish brown, and G4 line produced brown color of pods. The seed color of all of the lines exept G0 produced shiny green, while G0 line produce dull and shiny brownish green seed. The color characteristics of pods and seeds had an effect on the consumer taste, but it did not affect on the yield production. Therefore, this information could be used as germ-plasm resource to produce a new high yield cultivar.